1999
DOI: 10.1017/s0317167100000469
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Paraneoplastic Encephalomyelitis Associated with a Benign Ovarian Teratoma

Abstract: Background: Paraneoplastic encephalomyelitis (PEM) is a well characterized, and typically irreversible, paraneoplastic syndrome, usually associated with small cell lung cancer or other malignancy. We describe a case of a young woman with a benign ovarian teratoma who presented with a reversible PEM. Case report: A 24-year-old woman presented with a three week history of memory impairment, unusual behavior, personality changes, auditory hallucinations, hypersomnolence and binocular diplopia. On admission she wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Spontaneous complete recovery has been described, although very rarely [38,44]. Immunotherapy is largely ineffective [33], but several cases benefiting from antitumor treatment have been reported [33,38,45].…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Spontaneous complete recovery has been described, although very rarely [38,44]. Immunotherapy is largely ineffective [33], but several cases benefiting from antitumor treatment have been reported [33,38,45].…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Encephalitis due to production of auto-antibodies in the presence of ovarian teratoma was reported in 1999 [2] and subsequently determined to be due to antibodies against the N-methyl-D-aspartate (NMDA) subtype of glutamate receptor [3]. A later report documented the condition in patients free of teratoma, and found that such patients may fare worse [4].…”
Section: Introductionmentioning
confidence: 99%
“…First, myelitis is a very rare manifestation during anti-NMDAR-Ab encephalitis but has already been described [4-6]. In these 3 previous cases, all patients presented severe psychiatric or behavioural symptoms before the spinal cord syndrome and the encephalopathic symptoms remained prominent during all stages of the disease.…”
Section: Discussionmentioning
confidence: 97%